Decentralization â€“ Integrationâ€™s Challenge through Responsive Services - Dedaj, Gjon (Mediterranean Journal of Social Sciences, 2012)
This research is about the decentralization of social service in Albanian post communism, diversifying responsibilities, andresources through democratic institutions for integrity and Social Piece. Surveillances, Consultations, Interviews investigates relationshipbetween decentralization-centralization, public pressure for identity and indicatives of social exigency, diversity and high standards, factsand expectations in the representation map â€“ â€œgovernance hither civilâ€, welfare up growth, and protection of interested persons for fiscaltransfers of institutional budget. Politicize in social service conditions not coordinated and not consolidated evince the complexity ofâ€œdecentralization- centralized oversightâ€ irregularity and management of earning subsidy, effective public section, budget limitation forassured development. This studding brings the relationship of Decentralization with fineness governance, public orientation probable nonstability, short terms determines, long terms objectives, institutional partnered, planning agency without hierarchy, alternative ways thatwould be faced and tested according scientific criteria. The research includes the premise that decentralization favorites the marked ofpublic benefits, competition, denationalize, improvement of social politics against deepening polarization, hooking the elites, virtualduality of â€œrich â€“ poorâ€. Conclusions include the fact that we have communities without the service of social employee, philosophers,sociologist, diplomats, and physiologists for admonition of civil that take decisions, ways of clamor, social strengthen, and initiative tomake departments, flexibility and adoption conform national distinctions and global reflections â€œin one system that protect usâ€ developingsuccessful protective politics, e-learning contributes, licensee, euroatlantic standard dimensions.